Pursuing Public Health Benefit Within National Genomic Initiatives: Learning From Different Policies - Onstwedder, Suzanne M.; Jansen, Marleen E.; Leonardo Alves, Teresa; Cornel, Martina C.; Rigter, Tessel (Frontiers in Genetics, 2022)
Introduction: Population-based genomic research is expected to deliver substantial public health benefits. National genomics initiatives are widespread, with large-scale collection and research of human genomic data. To date, little is known about the actual public health benefit that is yielded from such initiatives. In this study, we explore how public health benefit is being pursued in a selection of national genomics initiatives. Methods: A mixed-method study was carried out, consisting of a literature-based comparison of 11 purposively sampled national genomics initiatives (Belgium, Denmark, Estonia, Finland, Germany, Iceland, Qatar, Saudi Arabia, Taiwan, United Kingdom (UK), and United States of America (USA), and five semi-structured interviews with experts (Denmark, Estonia, Finland, UK, USA). It was analyzed to what extent and how public health benefit was pursued and then operationalized in each phase of an adapted public health policy cycle: agenda setting, governance, (research) strategy towards health benefit, implementation, evaluation. Results: Public health benefit within national genomics initiatives was pursued in all initiatives and also operationalized in all phases of the public health policy cycle. The inclusion of public health benefit in genomics initiatives seemed dependent on the outcomes of agenda setting, such as the aims and values, as well as design of governance, for example involved actors and funding. Some initiatives focus on a research-based strategy to contribute to public health, while others focus on research translation into healthcare, or a combination of both. Evaluation of public health benefits could be performed qualitatively, such as assessing improved public trust, and/or quantitatively, e.g. research output or number of new diagnoses. However, the created health benefit for the general public, both short- and long-term, appears to be difficult to determine. Conclusion: Genomics initiatives hold the potential to deliver health promises of population-based genomics. Yet, universal tools to measure public health benefit and clarity in roles and responsibilities of collaborating stakeholders are lacking. Advancements in both aspects will help to facilitate and achieve the expected impact of genomics initiatives and enable effective research translation, implementation, and ultimately improved public health.